Trump's 19% Tariff Policy for Indonesia: Its Impact on Infrastructure Development and Food Independence - Wilda Sumarsyah; Silviani Joice Lengah; Nurjanna Ladjin; Dyah Ayu Suryaningrum; Ainil Mardiah (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This research is a qualitative study with a descriptive approach, an approach characterized by descriptive texts addressing the main topic. The main topics covered include the 19% Trump tariff, infrastructure development, and food independence. The data used in this study are secondary data obtained from various credible sources, such as scientific articles, magazines, books, and other sources commonly used in research. The data were analyzed through the stages of data collection, data reduction, data selection, and conclusion drawing. The conclusion in this article shows that Indonesia faces an increased expenditure burden compared to its previous level. This increased expenditure burden will also increase the financing burden. Indonesia is currently implementing efficiency measures. Potential investors may be reduced, and the author assumes that previously prioritized programs such as infrastructure development and food self-sufficiency will also be impacted.